Synthesis of oxa-bridged derivatives from Diels–Alder bis-adducts of butadiene and 1,2,3,4-tetrahalo-5,5-dimethoxycyclopentadiene - Khan, Faiz Ahmed; Parasuraman, Karuppasamy (Beilstein Journal of Organic Chemistry, 2010)
Bis-adducts of 1,2,3,4-tetrahalo-5,5-dimethoxycyclopentadiene and 1,3-butadiene, generated in situ from 3-sulfolene, have been synthesized in excellent yield. Ruthenium catalyzed oxidation of the bis-adducts followed by a one-pot transformation of the resulting α-diketone furnished oxa-bridged compounds. Unambiguous stereochemical assignments of both diastereomeric series are reported.
Keywords: Diels–Alder reactions; diketones; oxa-bridged derivatives; ruthenium; 3-sulfolene